1978
DOI: 10.1037/0033-2909.85.5.919
|View full text |Cite
|
Sign up to set email alerts
|

Metaphor: Theoretical and empirical research.

Abstract: Metaphor plays a major role in our understanding of language and of the world we use language to talk about.Consequently, theories of language comprehension and of language itself are incomplete if they do not handle the phenomenon of metaphor, and they are inadequate if they cannot.Traditional definitions and theories of metaphor are reviewed. It is suggested that they err in equating metaphors with comparisons rather than merely implicating comparisons. Empirical research is reviewed, revealing, for the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
79
0
5

Year Published

1981
1981
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(85 citation statements)
references
References 73 publications
1
79
0
5
Order By: Relevance
“…We emphasize instead the logical dependency of higher-order predicates on prior possession of their lower-order arguments. We therefore leave open the possibility that the progression may be governed by the degree of knowledge rather than by the child's stage of cognitive competence (e.g., Brown, 1989;Ortony, Reynolds, & Arter, 1978).…”
Section: The Career Of Similaritymentioning
confidence: 99%
See 1 more Smart Citation
“…We emphasize instead the logical dependency of higher-order predicates on prior possession of their lower-order arguments. We therefore leave open the possibility that the progression may be governed by the degree of knowledge rather than by the child's stage of cognitive competence (e.g., Brown, 1989;Ortony, Reynolds, & Arter, 1978).…”
Section: The Career Of Similaritymentioning
confidence: 99%
“…However, we differ from most prior theorists in an important respect. Rather than seek to explain the development of similarity in terms of global stages of competence, we will ask whether a weaker explanation will suffice, namely, accretion of knowledge (Brown, 1989;Brown & Campione, 1984;Gentner, 1977a, b;Ortony et al, 1978). We will return to comparisons with other views after elaborating our position.…”
Section: The Career Of Similaritymentioning
confidence: 99%
“…Finally, recent research using looking-time paradigms has suggested that even young infants are sensitive to identity relations (Tyrrell, Stauffer, & Snowman, 1991). These kinds of results have led most researchers to adopt the knowledge-change view, that whether children can recognize relational similarity in a domain depends chiefiy on their knowledge of that domain (Brown, 1989;Brown & DeLoache, 1978;Brown, Kane, & Echols, 1986;Carey, 1985Carey, , 1991Chen & Daehler, 1989;Chi, 1981;Chi, Feltovich, & Glaser, 1981;Crisafi & Brown, 1986;Gentiier, 1977aGentiier, , 1977bGentiier, , 1988Gentner & Rattermann, 1991;Goswami, 1991Goswami, , 1992Goswami & Brown, 1989;Ortony, Reynolds, & Arter, 1978;Vosniadou, 1987Vosniadou, , 1989.…”
mentioning
confidence: 99%
“…First, other studies have suggested that figurative language expressions may be comprehensible to children as young as first grade in certain conditions (e.g., Gentner, 1977;Home, 1966;Mayer, 1975;Pollio & Pollio, 1974;Reynolds & Ortony, Note 1). Second, Ortony (1981) and Ortony, Reynolds, and Arter (1978) have criticized much of the metaphor research on methodological grounds, arguing, for example, that the research has not adequately controlled for response bias or world knowledge. With respect to response bias their argument is that children may simply choose to respond literally even when they do in fact understand the metaphor.…”
mentioning
confidence: 99%